2016
DOI: 10.3389/fpsyg.2016.00046
|View full text |Cite
|
Sign up to set email alerts
|

Why are Some Games More Addictive than Others: The Effects of Timing and Payoff on Perseverance in a Slot Machine Game

Abstract: Manipulating different behavioral characteristics of gambling games can potentially affect the extent to which individuals persevere at gambling, and their transition to problematic behaviors. This has potential impact for mobile gambling technologies and responsible gambling interventions. Two laboratory models pertinent to this are the partial reinforcement extinction effect (PREE) and the trial spacing effect. Both of these might speed up or delay the acquisition and extinction of conditioned behavior. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 65 publications
(93 reference statements)
0
15
0
Order By: Relevance
“…We would expect to see other features common in gambling and substance addictions, such as a persistence in the behaviour after the reinforcing properties of the behaviour have been removed [9]. For example, the pattern of rewards in some games can lead some gamblers to continue to gamble long after they have stopped winning [10]. Similarly, alcohol-dependent people continue to drink long after they cease to enjoy drinking.…”
Section: Kardefelt-winther Et Almentioning
confidence: 99%
“…We would expect to see other features common in gambling and substance addictions, such as a persistence in the behaviour after the reinforcing properties of the behaviour have been removed [9]. For example, the pattern of rewards in some games can lead some gamblers to continue to gamble long after they have stopped winning [10]. Similarly, alcohol-dependent people continue to drink long after they cease to enjoy drinking.…”
Section: Kardefelt-winther Et Almentioning
confidence: 99%
“…Two participants whose data were analysed at a trial level were excluded from this analysis; in one case, the participant's phone was destroyed during the experimental period, and in the second, the participant could not be followed up. The number of gambles made during acquisition predicted the number of gambles during extinction (b = 0.0214, SE = 0.008, t = 2.728, p = 0.0117, multiple R 2 = 0.237, adjusted R 2 = 0.205) 1 . Table 1 shows how the decision to stop early is made based on outcome.…”
Section: Doi: 101159/000495663mentioning
confidence: 99%
“…The behavioural literature has identified that increases in the latency between reinforcements is associated with increased acquisition of learned behaviours [1,13], as well as non-reinforcing events (i.e., near-misses) that have structural and aesthetic similarities to wins [14,15]. When applied to gambling's random ratio schedule of reinforcement, there is the potential for an additive risk of harm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations